Accelerating the response of the education sector to HIV and AIDS in the Caribbean region : the Port-of-Spain documents (The Secretariat, UNESCO & the World Bank GeorgetownGY, 2007)
Presents the full text of the Port-of-Spain declaration which signified the commitment of the CARICOM Ministers of Education and other participants in the COHSOD meeting to renewed efforts at accelerating the education sector response to HIV and AIDS in the Caribbean; The Port-of-Spain Action Framework, which codified an emerging consensus among participants in the COHSOD meeting around a core set of actions to strengthen national HIV and AIDS responses by the education sector.
Keywords: EDUCATIONAL POLICY